Quản lí hoạt động phối hợp nhà trường - gia đình trong giáo dục đạo đức học sinh phổ thông: Thực trạng và đề xuất mô hình - Phan Doãn Hồng, Phan Doãn Hồng; Phan Doãn Hồng, Phan Doãn Hồng; Nguyễn Sỹ Thư, Nguyễn Sỹ Thư (Tạp chí Giáo dục, 2026)
In the context of educational reform in Vietnam, strengthening coordination between schools and families in students' moral education is becoming increasingly necessary. This study analyze the current situation of management of school-family coordination in the moral education of students in private secondary schools. Data was collected through a questionnaire survey of 207 administrators, homeroom teachers, and parents of students at nine private secondary schools in Ho Chi Minh City. The research results show that coordination between schools and families primarily focuses on handling emerging situations and is neither proactive nor regular, nor guided by a clear management orientation. From a management perspective, the PDCA cycle (plan - do - check - act) has not been fully implemented, with limitations in the checking, evaluation, and adjustment stages; at the same time, the coordination mechanism among participating forces is not truly specific and unified. Based on the survey results, the study proposes a model for managing collaborative activities between schools and families using a systems approach combined with the PDCA cycle to enhance the consistency, continuity, and effectiveness of the moral education process for students. The research results provide a practical basis for improving the management of collaborative activities between schools and families in general education institutions.